An Innovative approach of meteorological observation integration to develop state-of-the-art web based visualization tool (MAUSAM, 2024)
Nowcasting plays a crucial role in assessment of current conditions of the atmosphere. Short-term prediction (nowcasting) of high-impact weather events can lead to significant improvement in warnings. Therefore, development of some tools through objective methods has immense importance in upgrading the capabilities of India Meteorological Department. At present, conventional subjective methods are running which are not much accurate. The biggest limitation is non-availability of various datasets at a same platform which makes nowcasting redundant and inefficient. Thus a robust web based tool is required which has ability to Integrate all available dataset at a same place in real time. This web based tool will be of great help to forecaster for delivering best and accurate state of the atmosphere in current condition. For development of this tool various datasets like radar, satellite, upper air sounding data and lightning data etc has been utilized. By using this tool as an integrated display, forecaster shall be able to analyze small-scale features present in a small area such as a city and make an accurate forecast for the next few hours. This tool is capable of providing warning to the public for hazardous, high-impact weather phenomenon including tropical cyclones, thunderstorms, lightning strikes and destructive winds as well. This paper is an attempt for development of a web based visualization tool by integration of various near-real time weather observation datasets for nowcasting purpose.